2017
DOI: 10.22214/ijraset.2017.2098
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Use of Copper Slag and Recycled Aggregate as a Fine Aggregate in Concrete

Abstract: Conservation of natural resources and preservation of environment is the essence of any modern development. In last few decades, construction activities increase rapidly. Itsss require more raw materials and it will result in shortage of material in future. Now a days there is trend of recycling and reusing material, which is partial solution of this problem. Also, Industrial wastes are used as raw material. It reduces the consumption of natural resources. Copper slag and recycled aggregate are the industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The optimum percentage was found to be at 7.5%. From the research paper [4], it was concluded that copper slag and recycled aggregates might be used as partial replacements of fine aggregate which are waste products. Copper slag with lesser water absorption and higher strength than fine aggregate can be effective in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum percentage was found to be at 7.5%. From the research paper [4], it was concluded that copper slag and recycled aggregates might be used as partial replacements of fine aggregate which are waste products. Copper slag with lesser water absorption and higher strength than fine aggregate can be effective in concrete.…”
Section: Introductionmentioning
confidence: 99%